The Implementation of Al-Qur'an and Hadith Learning in Enhancing Students' Character at MTs Yaqin 2 Pemondah - M. Hilmi Tantowi (Formad English Foundation NTB Jakarta, 2024)
This study examines the implementation of Qur'an and Hadith learning in enhancing students' character at MTs Yaqin 2 Pemondah. The research employed a quasi-experimental design with a control group to evaluate the impact of Qur'an and Hadith education on character traits such as discipline, honesty, and responsibility. A sample of 26 students was divided into experimental and control groups, and data were collected through pre-test and post-test assessments, qualitative observations, and interviews. The results revealed a significant improvement in the character scores of the experimental group, with a mean post-test score of 85.6 compared to 68.4 in the control group. Statistical analysis using a paired t-test confirmed the significance of the findings (p < 0.001). Qualitative data further indicated positive behavioral changes, as observed by teachers and peers. The study highlights the importance of incorporating Qur'anic and Hadith education into school programs to foster students' moral and ethical development. These findings provide valuable insights for educators and policymakers in designing effective religious-based character education strategies. Future research could explore the broader applicability of these findings across different educational settings and student demographics.